Estimates of global and regional prevalence of neural tube defects for 2015: a systematic analysis. Issue 1 (24th January 2018) - Blencowe, Hannah; Kancherla, Vijaya; Moorthie, Sowmiya; Darlison, Matthew W.; Modell, Bernadette
Abstract: Neural tube defects (NTDs) are associated with substantial mortality, morbidity, disability, and psychological and economic costs. Many are preventable with folic acid, and access to appropriate services for those affected can improve survival and quality of life. We used a compartmental model to estimate global and regional birth prevalence of NTDs (live births, stillbirths, and elective terminations of pregnancy) and subsequent under‐5 mortality. Data were identified through web‐based reviews of birth defect registry databases and systematic literature reviews. Meta‐analyses were undertaken where appropriate. For 2015, our model estimated 260, 100 (uncertainty interval (UI): 213, 800–322, 000) NTD‐affected birth outcomes worldwide (prevalence 18.6 (15.3–23.0)/10, 000 live births). Approximately 50% of cases were elective terminations of pregnancy for fetal anomalies (UI: 59, 300 (47, 900–74, 500)) or stillbirths (57, 800 (UI: 35, 000–88, 600)). Of NTD‐affected live births, 117, 900 (∼75%) (UI: 105, 500–186, 600) resulted in under‐5 deaths. Our systematic review showed a paucity of high‐quality data in the regions of the world with the highest burden. Despite knowledge about prevention, NTDs remain highly prevalent worldwide. Lack of surveillance and incomplete ascertainment of affected pregnancies make NTDs invisible to policy makers. Improved surveillance of all adverse outcomes is needed to improve the robustness of total NTD prevalence estimation, evaluate effectiveness of prevention through folic acid fortification, and improve outcomes through care and rehabilitation.